Nature and magnitude of wave loadings at Seawave Slot-cone Generators. (1st February 2015) - Buccino, M.; Vicinanza, D.; Salerno, D.; Banfi, D.; Calabrese, M.
Abstract: The Seawave Slot-cone Generator (SSG) is a wave energy converter based on the overtopping principle, which has collected a good deal of funds in the last years, from both public and private investors. Although its functional response has been extensively researched, practically no tools exist for the structural design. Based on the results of regular wave experiments conducted at the University of Naples Federico II (Italy), a number of design equations have been derived, which permit to estimate the magnitude of the wave pressures acting onto the outer face of the device, along with the respective rise times. The reliability of the predictive methods have been then verified against the random wave experiments ofVicinanza and Frigaard (2009) . Highlights: 2-D model tests on Seawave Slot-cone Generator (SSG) wave energy converter. Probabilistic approach to predict wave pressures. Scale effect discussion.